DETEKSI DINI KRISIS PERBANKAN INDONESIA: IDENTIFIKASI VARIABEL MAKRO DENGAN MODEL LOGIT - Oktavilia, Shanty (JEJAK: Jurnal Ekonomi dan Kebijakan, 2008)
Indonesia suffered from banking crisis for several times. It was the effect of the worst crisis occurredin 1997. Actually, Bath Thailand which plunged into 27,8% at the third quarter of the year 1997 was thebeginning problem that caused Asia currency crisis. This study analyzes the influence of macro indicatoras an early warning system by using logit econometrics model for predicting the possibilities of bankingcrisis that may occur in Indonesia.Kewords: Banking Crisis, macro economic indicator, EWS-logit model